Marc Chagall - Welton, Jude. (New York : F. Watts, 2003)
Examines the life and work of the Russian-born painter, describing and giving examples of his art.
Includes index.
6.4
5-8
Keywords: Chagall, Marc, -- 1887-; Artists -- Biography